Hydrogel-Based Bioinks for 3D Bioprinting in Tissue Regeneration - Ramiah, Previn; du Toit, Lisa C.; Choonara, Yahya E.; Kondiah, Pierre P. D.; Pillay, Viness (Frontiers in Materials, 2020)
Three-dimensional (3D) printing of biomaterials provides an interesting alternative for the production of allograft tissues and organs to circumvent the incidences of donor scarcity and organ shortages. With the current deficit of readily available and viable organs for transplantation, the medical sector is faced with an increasing demand for organs and the shortfall in supply. Over the past decades, tissue engineering and regenerative medicine continue to provide alternative strategies for artificial tissues and organs. Current research shows that employing hydrogels as a cell-laden bioinks for the fabrication of 3D tissue constructs enables a lack of immunogenicity, since the hydrogel-based bioink is patient-specific and derived from biopolymers that demonstrate excellent biocompatibility and biodegradability, decreased organ rejection, increased organ viability and enhanced the supply in accordance to the demand. While sufficient evidence directs researchers to conclude the safe and efficacious process of seeding cells, biomolecules and biomaterials using 3D bioprinting, there are multiple limitations, which requires significant attention, such as cost, volumetric bioprinting, integrity and strength of biomaterials as well as multi-cellular and multi-material bioprinting. In this review, the focus is on the applications of hydrogels as bioinks employed in 3D bioprinting, and where applicable, considerations of note and challenges encountered. This review proposes to highlight the progress forged in this area, but also the limitations of hydrogel-based bioink investigations to date and the need for further multidisciplinary investigation and progression to the stage of clinical testing of human-scale tissue constructs.